2016
DOI: 10.1007/978-3-319-25079-3
|View full text |Cite
|
Sign up to set email alerts
|

Scattering of Particles and Radiation in Astrophysical Environments

Abstract: The scattering of atoms, molecules, and radiation are the most fundamental mechanisms of energy-momentum transfer in nature. Fluxes of particles and radiation may deposit energy into a system as well as be emitted, giving deep insight into fundamental processes occurring within the system. Astrophysics, in particular, may benefit from collisional modeling and transport as remote viewing of distant objects is the only option for the vast majority of astrophysical objects. Practically all interaction processes b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 108 publications
(187 reference statements)
0
3
0
Order By: Relevance
“…In astrophysical environments, it is well known that dust and ice NPs efficiently scatter X-rays due to their grain geometric sizes being on the same scale as the photon wavelengths 31 , 32 . In such studies, the classical Mie model is used as an approximation in determining differential and total scattering cross sections for nano-sized particles 32 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In astrophysical environments, it is well known that dust and ice NPs efficiently scatter X-rays due to their grain geometric sizes being on the same scale as the photon wavelengths 31 , 32 . In such studies, the classical Mie model is used as an approximation in determining differential and total scattering cross sections for nano-sized particles 32 .…”
Section: Resultsmentioning
confidence: 99%
“…In order to assess the impact of the NP size on the Mie scattering of X-rays, we simulated the Mie-scattering process for spherical Bi 2 O 3 NPs with diameters ( d ) of 20, 40 and 100 nm. The NP size is crucial for detector sensitivity as NPs in the quantum dot regime (<10 nm) lead to indirect X-ray detection 34 , while large nanoparticles (≥100 nm) reduce the extraction probability for charges generated within the NP and also reduce the differential scattering cross section as the particle size becomes very much greater than the X-ray wavelength 31 . These simulations do not take into consideration the effect of an ensemble of NPs, particle size distribution of the NPs, the formation of NP clusters, or deviations in the aspect ratio from a simple spherical geometry.…”
Section: Resultsmentioning
confidence: 99%
“…They found that the synthesized model is better compared to the earlier model with two Maxwell-Boltzmann components; however, they found that their reduced χ 2 measure is still significantly too high, suggesting missing physical effects in their analysis. In this paper, we focus on ISN hydrogen atoms, but a simple estimation of the momentum transfer effect can be obtained assuming the same shape of the differential cross section in He 0 -He + charge exchange collisions as for proton -hydrogen atom collisions for the same energy per mass (Lewkow et al 2012;Lewkow 2016). Based on this estimation, the distribution of secondary ISN helium atoms is presented in Figure 11 for the relative parent population velocity of 15 km s -1 , and temperatures of He + ions and He atoms of 15000 K and 7500 K, respectively.…”
Section: Secondary Isn Helium Atomsmentioning
confidence: 99%